2002
DOI: 10.1104/pp.008649
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis CYP98A3 Mediating Aromatic 3-Hydroxylation. Developmental Regulation of the Gene, and Expression in Yeast

Abstract: The general phenylpropanoid pathways generate a wide array of aromatic secondary metabolites that range from monolignols, which are ubiquitous in all plants, to sinapine, which is confined to crucifer seeds. The biosynthesis of these compounds involves hydroxylated and methoxylated cinnamyl acid, aldehyde, or alcohol intermediates. Of the three enzymes originally proposed to hydroxylate the 4-, 3-, and 5-positions of the aromatic ring, cinnamate 4-hydroxylase (C4H), which converts trans-cinnamic acid to p-coum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 59 publications
3
54
0
2
Order By: Relevance
“…It is accompanied by a strong increase in p-coumaroyl esters, H lignin units, and flavonoids. This confirms the central role of CYP98A3 as the C3#H in the general phenylpropanoid pathway (Schoch et al, 2001;Franke et al, 2002aFranke et al, , 2002bNair et al, 2002). However, the persistence of detectable amounts of SM in cyp98A3 null plants and the presence of G and S lignin units mainly in their roots support the hypothesis of an alternative meta-hydroxylase pathway independent of CYP98A3.…”
Section: Cyp98a3 T-dna Insertion and Cosuppression Mutants Show Drastsupporting
confidence: 55%
See 1 more Smart Citation
“…It is accompanied by a strong increase in p-coumaroyl esters, H lignin units, and flavonoids. This confirms the central role of CYP98A3 as the C3#H in the general phenylpropanoid pathway (Schoch et al, 2001;Franke et al, 2002aFranke et al, , 2002bNair et al, 2002). However, the persistence of detectable amounts of SM in cyp98A3 null plants and the presence of G and S lignin units mainly in their roots support the hypothesis of an alternative meta-hydroxylase pathway independent of CYP98A3.…”
Section: Cyp98a3 T-dna Insertion and Cosuppression Mutants Show Drastsupporting
confidence: 55%
“…Three hydroxylations are necessary to form these three units, which are catalyzed by three different cytochrome P450 monooxygenases: cinnamate 4-hydroxylase (C4H or CYP73), p-coumaroyl ester 3#-hydroxylase (C3#H or CYP98), and ferulate 5-hydroxylase (F5H or CYP84; Humphreys and Chapple, 2002). The 3-hydroxylation step was only recently shown to involve the cytochrome P450 CYP98A3 in Arabidopsis (Schoch et al, 2001;Franke et al, 2002aFranke et al, , 2002bNair et al, 2002). The meta-hydroxylation (or 3-hydroxylation) is not catalyzed on the free p-coumaric acid as anticipated, but on its conjugates with shikimic or quinic acids (Schoch et al, 2001).…”
mentioning
confidence: 99%
“…EGSBRT3314B10.g (30 reads, 17 in WD2) is a full-length gene and EGEQCL2001E08.g (11 reads, 8 in WD2) encodes 253 N-terminal amino acids of the protein. The protein encoded by cluster EGSBRT3314B10.g shows 77.2% sequence identity to the functionally characterized A. thaliana C3H (Schoch et al, 2001;Franke et al, 2002;Nair et al, 2002), while the peptide encoded by EGEQCL2001E08.g shows an identity of 70.7%. PSORT indicates ER localization for both proteins.…”
Section: P-coumarate 3-hydroxylase -C3hmentioning
confidence: 99%
“…CYP98A3, a candidate gene for C3H activity, converted p-coumaroyl shikimate and p-coumaroyl quinate into their corresponding caffeic acid conjugates and did not prefer p-coumaric as a substrate (Schoch et al, 2001). Further, characterization of Arabidopsis, alfalfa and poplar CYP98A3 by mutant or transgenic approaches showed that CYP98A3 is involved in lignification (Franke et al, 2002;Nair et al, 2002;Reddy et al, 2005, Coleman et al, 2008. A gene that encodes for hydroxycinnamoyl-CoA shikimate/quinate hydroxycinnamoyl transferase (HCT) activity, which converts p-coumaryl CoA to p-coumaroyl shikimate or p-coumaroyl quinate was also identified and its role in lignin biosynthesis was unequivocally established (Hoffmann et al, 2003;.…”
Section: Cell Wall Biosynthesismentioning
confidence: 99%